Application of Data Mining to Predict Procurement of Office Writing in Al-Ikhwan Middle School using Naïve Bayes Method - Aida Sopia; Muhammad Syahrizal (STMIK Budi Darma, 2020)
Office stationery (ATK) is now a necessity for almost everyone, especially for corporate instances or educational institutions. The need for office stationery is often an unexpected need to buy, this is what makes some educational institutions overwhelmed in doing their work, when they find out their office stationery is out of stock, so it is not uncommon to make work in company or institutional instances education is not completed on time, one of the ways to be more efficient is by implementing data mining to predict the purchase of office stationery (ATK) at the company or educational institution's intents, especially at the AL IKHWAN Middle School in Tanjung Morawa. The Naive Bayes method is used to analyze data in pattern recognition and predict purchase of office stationery (ATK) at AL IKHWAN Middle School in Tanjung Morawa. The data needed is the data for the purchase of office stationery (ATK) last month as test data, calculated from the date of the first purchase until the expiry date of office stationery (ATK) at AL IKHWAN Middle School in Tanjung Morawa. The results of this study are to be able to predict whether the office stationery (ATK) at AL IKHWAN Middle School in Tanjung Morawa can be bought back, or it can still be used for a long time, and if more than four types of stationery at the AL IKHWAN Middle School in Tanjung Morawa the lack of writing instruments from the two then the purchase of new stationery is feasible to do, from the amount of data occurring out of stationery